Catalisadores para produção de hidrogênio a partir de reações entre etanol e vapor d'água - Alonso, Christian Gonçalves (2008)
Hydrogen production has been extensively researched aiming at meeting the demand for alternative energy sources which respect the new global order of management of polluter emission and the use of natural resources. In this context, ethanol and water molecules can be considered promising for H2 storage and supply via ethanol steam reforming reaction, which stands out as a clean and renewable process. However, studies of this process in micro-reactors systems (mg) have demonstrated a wide range of possible pathways for the reaction with the formation of intermediary products, which can react among themselves affecting the catalyst performance and making the process impracticable. In this work, the selection/development of catalysts were conducted aiming the H2 production through the process of ethanol steam reforming in reactors systems of higher scale (7 g) at temperature of 300 °C and atmospheric pressure. From the results about the process of ethanol steam reforming of the catalysis group of DEQ/UEM obtained in micro-reactor and in literature reports, Cu, Pd and Ru were selected as components for the active phase and Nb2O5, CeO2, La2O3 and TiO2 as catalysts supports. Prepared by impregnation from alcoholic solutions of chloride salts precursors of Cu, Pd and Ru, all the supports and catalysts were characterized by X-ray fluorescence spectrometry, energy dispersive X-ray spectrometry, thermogravimetric analysis simultaneous to differential thermal analysis, X-ray diffraction, textural analysis by adsorption/desorption isotherms of N2, temperature programmed reduction and temperature programmed desorption of NH3. The results of characterization revealed the differences generated by the addition of a second metal to the active phase or by the use of a second oxide creating mixed supports. The TG/DTA analyses indicated that the calcination of catalytic precursors was enough to remove the solvents and waste of the reagents used in the catalysts synthesis. By the XRF and EDX analyses the differences between the contents of metals in the active phase of the catalysts in their total volume and the superficial contents were determined, making the results for materials with the Ru/Nb2O5 combination evident, in which Ru was not detected through EDX, indicating then its penetration in more internal layers. The results of XRD, textural and TPR analyses showed the sum of effects of the oxides mixture in catalysts and mixed supports with the material containing La2O3 presenting peaks related to unstable structures. Significant differences in the relative acidity of the catalysts were observed from the mixture of supports and metals of the active phase without a linear effect though. The selection of catalysts was subdivided into two phases: active phase evaluation; and evaluation of supports with the best active phase. In both phases, the catalysts tests were carried out at 300 °C under atmospheric pressure with H2O/C2H5OH molar ratio equals to 10/1 and W/FA0 equals to 17,16 (gcat h/mol). The 0,5% Pd-0,5% Ru/La2O3-Nb2O5 (PRLN) and 0,5% Pd-0,5% Ru/Nb2O5-TiO2 (PRNT) catalysts demonstrated better performance in H2 production at 300 °C and were selected for tests at temperatures of 375 and 450 °C with the most promising results obtained for the PRLN catalyst at 450 °C. The effect of the H2O/C2H5OH molar ratio and the reagent mixture flow rate was considered in tests with the PRLN catalyst at 450 °C, allowing the efinition of the system operational conditions for stability evaluation followed by reactivation with steam and catalytic retest. All the catalysts including the pure supports demonstrated activity to ethanol conversion at 300 °C producing H2, CH4, CO, CO2, C2H4, C2H6, C2H4O, (C2H5)2O and coke, being the latter the main responsible for the catalyst deactivation. The catalysts based on noble metals (Pd and/or Ru) presented better performance in H2 production. The use of mixed supports led to the increase of catalytic activity with alterations in selectivity. The results showed a great diversity of possible reactions under the conditions studied. Tests with PRLN catalyst presented maximum activity at 450 °C. However, this catalyst suffered deactivation during the investigation period with ethanol conversion decreasing from 90% to 25% after 30 h of test and stabilization occurring until 76 h. The catalyst recovered its activity when it was activated with steam at 450 °C, but after 8 h of reaction it deactivated reaching ethanol conversion equals to 30%.